Real-time remote monitoring and control system for underground pipelines - Noor Hazim Abdulwahab; ‪Ali Ahmed Abed‬‏; Mohammed Ali Jaber (International Journal of Electrical and Computer Engineering (IJECE), 2022)
Underground pipelines suffer from corrosion in soil layers, and this corrosion is accelerated with the increasing of soil thickness due to more water contained. Cathodic protection (CP) is one of the most common methods for controlling corrosion of metals. Its popularity returns to the fact that CP system is simple, cheap, and suitable for many industrial applications. The drawback of the available CP systems is the need to go to the site for gathering data using classical instruments and methods, which is tedious, dangerous, uneconomic, and inaccurate. The main objective of this paper is to present a real-time remote monitoring and control (RT-RMC) system for any CP platform. The work started with implementation of an industrial-like CP prototype to realize the desired task. The implemented CP system consists of two famous CP methods, the sacrificial anodes (SACP) and the impressed current (ICCP). After that, the RT-RMC system is implemented with two techniques, global system for mobile communications(GSM), and web of things (WoT) to facilitate monitoring and control tasks. Experimental results are obtained for voltage and current measurements with different environments, disturbance, and pipe coatings.